Markers of the epithelial-mesenchymal transition in cells of endometrial carcinoma - Nesina, I.P.; Iurchenko, N.P.; Buchynska, L.G. (Experimental Oncology, 2018)
Aim: To study the expression of adhesion markers (E-cadherin, β-catenin and vimentin) associated with epithelial-mesenchymal transition (EMT) and their role in progression of endometrial carcinoma (EC). Materials and Methods: Expression of E-cadherin, β-catenin and vimentin was studied immunohistochemically in the samples of surgical material of 55 EC patients stage I–III. The proliferation index was determined by flow cytometry. Results: In the group of vimentin-negative EC, tumors of low differentiation grade and deep invasion in myometrium as well as high expression of E-cadherin and β-catenin prevailed compared with the cases with high expression of vimentin. In addition, in EC with high expression of vimentin, an increase in the number of cells with expression of E-cadherin in the cytoplasm (78.9 ± 3.6%) and β-catenin with cytoplasmic-nuclear localization (73.7 ± 3.2%) was observed compared with these indices in vimentin-negative tumors (45.4 ± 4.2%, p < 0.001 and 54.5 ± 2.6%, respectively, p < 0.005), which may indicate EMT-associated changes in EC with high expression of vimentin. Conclusions: The progression of the endometrioid carcinoma may occur in the setting of various molecular changes, in particular, with decreased expression of E-cadherin and β-catenin and high expression of vimentin, or in the absence of vimentin, utilizing other mechanisms of regulation of proliferative and metastatic potential. Key Words: endometrial cancer, proliferation index, E-cadherin, β-catenin, vimentin.